Zwei Fotografien in einer Klarsichthülle in einem Ordner. Auf den Fotografien erkennt man die nachgebauten Masken (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2013)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Art; Photographs; Artists; Masks; Iwalewahaus; Cultural Centre; Performing Arts Center